STRATEGI PUBLIC RELATION UNTUK MENINGKATKAN AWARENESS DAN KETERLIBATAN MASYARAKAT DALAM KEGIATAN KEAGAMAAN - Ningrum, Deviana Setia (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
Religious activities have an important role in building the morale and spirituality of the community, but often do not receive optimal attention and involvement from the community. This article discusses Public Relations (PR) strategies in increasing public awareness and involvement in religious activities, with a focus on effective communication approaches. The discussion included the role of Public Relations (PR) in building awareness through information media, the application of interpersonal and digital communication techniques, and the management of trust-based relationships with the target community. The case study of the Santri Smart Competition in Jorong Kubu Rajo is an example of the implementation of this strategy, where active participation has been successfully increased through a planned Public Relations (PR) campaign. The results of the analysis show that collaboration between traditional and digital media, packaging of relevant messages, and post-activity evaluation can increase the success of religious programs. This article recommends a strategic PR approach to increase participation and create a wider social impact in religious activities.